Association between encounter frequency and time to blood pressure control among patients with newly diagnosed hypertension: a retrospective cohort study. Issue 3 (16th February 2018) - Sherman, Liliana; Pelter, Mitchell A.; Deamer, Robert L.; Duan, Lewei; Batech, Michael
Abstract : This retrospective cohort study of 95 957 patients from a large integrated healthcare organization was conducted to examine whether the frequency and intervals between outpatient encounters were associated with achieving blood pressure (BP) control. Patients were followed up until they were censored or achieved BP control up to 1 year. Additionally, this study examined the time to BP control. On average, follow‐up was significantly longer in patients with uncontrolled BP at 292.9 days compared with 232.2 days in those with BP control. The controlled BP group had significantly more encounters on average compared with the uncontrolled BP group (4.1 vs 3.1, standardized difference 0.33). As the number of days increased between encounters from the 1 to < 14 days, there was a consistently lower likelihood of achieving BP control. Encounter intervals of ≥180 days were associated with the lowest likelihood of achieving BP control. These findings suggest that there may be an optimal number of encounters to benefit patients with hypertension.